FACTORS OF POLLUTION OF THE GEOECOLOGICAL CONDITION OF AGGLOMERATIONS (ON THE EXAMPLE OF FERGANA-MARGILAN AGGLOMERATION) (Scientific journal of the Fergana State University, 2024)
The article focuses on the causes and consequences of the main geoecological problems that are occurring in the agglomerations of our country as well as in many large cities of the world in the current era of globalization. These processes are explained on the example of the Fergana-Margilan agglomeration that is forming in our country. The fact that these two cities have a large population and their natural geographical location is located in the Fergana Valley is analyzed, and the negative consequences of these factors are briefly studied. Also, the geo-ecological factor that has the biggest impact on the geo-ecological condition of these two big cities has been researched and a number of proposals have been made to prevent pollution.